Effects of dark malts, dry hopping, and filtration on xanthohumol content and bioactivity of American India Pale Ales - Henley, Twila Jean, author; Stone, Martha, advisor; Vanamala, Jairam, advisor; Bunning, Marisa Lee, 1954-, committee member; Avens, John S., committee member; Reddivari, Lavanya, committee member; Stonaker, Frank H., committee member (Colorado State University. Libraries, 2011)
Xanthohumol (XN), a prenylated chalcone found in hops (Humulus lupulus L.) has been shown to possess a wide spectrum of beneficial properties including anti-oxidant, anti-proliferative, pro-apoptotic, anti-inflammatory, anti-bacterial, anti-viral, and anti-malarial activities. Efforts have been made to increase the amount of XN in beers by modifying certain brewing ingredients and procedures. However, the effects of modifications such as addition of dark malts, dry hopping, and DE filtration on XN content and the biological activity of American India Pale Ales (IPAs) are not known. In this study, different brands of IPAs with and without addition of dark/roasted malts, dry hopping, and filtration and one non IPA as a standard were analyzed for XN, isoxanthohumol, total phenolic content, and antioxidant capacity. Isolated beer compounds and selected whole beer matrixes were used to determine the synergistic effect of beer compounds on proliferation and apoptosis of HCT 116 p53 +/+ colon cancer cells. No XN was found in the standard, and the XN content in IPAs ranged from 0.00 to 12.69 mg/L. A heavily dry hopped IPA made with increased amounts of dark malt contained higher amounts of XN compared to other IPAs. The use of dark malts was protective against the removal of XN and other phenolics after diatomaceous earth (DE) filtration and dry hopping increased XN content in beer. Whole beer matrixes with greater levels of XN suppressed proliferation and elevated apoptosis in colon cancer cells compared with isolated XN and/or IX, indicating that the biological effect of XN can be bolstered in the presence of other beer compounds.